2020
DOI: 10.1039/c9cc08717f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically induced crystallization of amorphous materials in molten MgCl2: boron nitride and hard carbon

Abstract: A novel and versatile strategy toward the amorphous-to-crystalline transformation of boron nitride was developed through an electrochemical pathway using molten MgCl2 at low temperature (750 °C) and can be extended for transformation of amorphous carbon to graphite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Activated coconut charcoal (ACC) from coconut waste (Fisher Scientific, 50–200 mesh) and anhydrous CaCl 2 (Sigma-Aldrich, 97%) were used as received. The salts were predried to remove the moisture following the protocol described in the literature …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Activated coconut charcoal (ACC) from coconut waste (Fisher Scientific, 50–200 mesh) and anhydrous CaCl 2 (Sigma-Aldrich, 97%) were used as received. The salts were predried to remove the moisture following the protocol described in the literature …”
Section: Methodsmentioning
confidence: 99%
“…Several approaches (oxidizing the surface, increasing the interlayer distance, creating pores, coating the surface to counteract the volume expansion) have been tried to modify the graphite structure to enhance the fast-charging performance. , However, these approaches either do not meet the required criteria or are economically not viable to apply on already costly graphite. Our group has developed the low-temperature electrochemical transformation of amorphous carbon precursors to graphite ,, with high crystallinity, porosity with a highly tunable nanoflake architecture, and interlayer spacing that can facilitate faster lithium diffusion and relieve the stress created by ion intercalation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When it is used as the anode material of a lithium-ion battery, it can provide a reversible capacity of about 280 mA h g −1 at the charge and discharge rate of 5 C (1.86 A g −1 ). Zhang put forward the corresponding concept of "electrochemical graphitization" in research that found that cathodic polarization in molten chloride can graphitize amorphous carbon at about 820 • C, and this method has been proved to be suitable for all amorphous carbon, providing a basis for preparing sustainable graphite as a high-performance anode [132][133][134][135][136][137][138]. To sum up, carbon nanotubes, graphene and carbon microspheres have great application potential in lithium-ion batteries, but they also have certain advantages and disadvantages.…”
Section: Application Of Carbon Microspheresmentioning
confidence: 99%